DEVELOPMENT OF TEACHER PERFORMANCE EVALUATION MODELS OF INCLUSIVE AND REGULAR SCHOOLS - Yuyun Yuningsih Ratnasari; Nurwalidainismawati; Abas Oya; Tri Nurrahmania (Universitas Majalengka, 2024)
The objective of this study is to develop a performance evaluation model for teachers in regular and inclusive schools. The research followed stages of analysis, design, development, implementation, and evaluation. Data were collected through observation, documentation, and questionnaires and analyzed using both descriptive and qualitative methods. The Gregory formula was used to analyze expert validation, and confirmatory factor analysis (CFA) was employed to assess the test results. Findings indicate that the evaluation instrument meets validity criteria, with loading factor values ranging from 0,7 to 1.00 (>0.7) for SDN Doridungga. Meanwhile, SLB Wihdatul Ummah Donggo with loading factor values ranging from -0.074 to 0.979 (>0.7). Confirmatory Factor Analysis (CFA) shows that the model for SDN Doridungga has a good fit with a Standardized Root Mean Square Residual (SRMR) value of 0.001, while the model for SLB Wihdatul Ummah Donggo shows an SRMR value of 0.258, which indicates that the model is not fit.